2017
DOI: 10.1016/j.jes.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter (PM2.5) exposure season-dependently induces neuronal apoptosis and synaptic injuries

Abstract: Epidemiological studies have shown that particulate matter 2.5 (PM) not only increases the incidence of cardiopulmonary illnesses but also relates to the development of neurodegenerative diseases. Considering that PM is highly heterogeneous with regional disparity and seasonal variation, we investigated whether PM exposure induced neuronal apoptosis and synaptic injuries in a season-dependent manner. The results indicated that PM altered the expression of apoptosis-related proteins (mainly bax and bcl-2), acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Kulas et al () found that prenatal exposure to PM2.5 in mice led to elevated SYP expression and unchanged PSD95 expression in the hippocampus of male offspring. Zhang et al () reported that prenatal PM2.5 exposure in mice decreased postsynaptic densities of membranes and the number of synaptic vesicles in the cerebral cortex of offspring, and an in vitro study suggested that PM2.5 exposure reduced PSD95 expression in cortical neurons (Chen, Li, & Sang, ). These results suggested that PM2.5 exposure during early life might change synaptic structural plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Kulas et al () found that prenatal exposure to PM2.5 in mice led to elevated SYP expression and unchanged PSD95 expression in the hippocampus of male offspring. Zhang et al () reported that prenatal PM2.5 exposure in mice decreased postsynaptic densities of membranes and the number of synaptic vesicles in the cerebral cortex of offspring, and an in vitro study suggested that PM2.5 exposure reduced PSD95 expression in cortical neurons (Chen, Li, & Sang, ). These results suggested that PM2.5 exposure during early life might change synaptic structural plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…The PM 2.5 sampling point was located in Taiyuan (112°21–34′E longitude, 37°47–48′N latitude) of Shanxi Province. The samples were collected onto quartz filters (Φ90 mm, Munktell, Falun, Dalarna, Sweden) with PM middle-volume air samplers (TH-150CIII, Wuhan, China) from November 2012 to February 2013 according to our previously reported conditions [ 84 ], and the PM characterization was presented in our recently published work (Additional file 1 : Table S1) [ 85 ]. The collected PM 2.5 was transferred into aqueous suspension by soaking the PM 2.5 -loaded filters in Milli-Q deionized water for 30 min, followed by vortexing (5 min) and sonication (30 min).…”
Section: Methodsmentioning
confidence: 99%
“…Concerning to about PM 2.5 exposure induced neuronal apoptosis, evidence from mouse model of gestational PM 2.5 exposure showed neuronal apoptosis in hippocampus of mice offspring [24]. In vitro data also showed that PM 2.5 exposure season-dependently induced neuronal apoptosis and synaptic injuries [9]. From our results, TUNEL positive cells were obviously increased in CA1 area of the hippocampus from mice exposed to PM 2.5 for 24 weeks, indicating elevated neuronal apoptosis rate by PM 2.5 exposure ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…PC12 cells were cultured in DMEM (BBI Life Sciences, China) supplemented with 10% fetal bovine serum (FBS) (Thermo Fisher Scienti c, USA), 1% penicillin-streptomycin (BBI Life Sciences, China), and maintained in an incubator at 37 °C with 5% CO 2 . Primary hippocampal neurons were prepared from the brains of C57BL/6 at postnatal day 1 as previously described [43] and brie y described in supplementary materials.…”
Section: Brain Slice Preparation and Tunel Testmentioning
confidence: 99%
See 1 more Smart Citation